Serum vitamin D status in children and adolescence with diabetes according to season and age - Sung Su Jung; Min Sun Kim; Dae Yeol Lee (Korean Society of Pediatric Endocrinology, 2014)
PurposeIt is known that children with diabetes have more severe vitamin D deficiency than healthy children. This study aimed to investigate serum vitamin D status and analyze the relationships between serum vitamin D levels and clinical parameters in children with diabetes.MethodsWe checked serum vitamin D levels of children with diabetes aged below 18 years who were treated at our Department of Pediatrics between December 2011 and February 2012 (winter) as well as between June 2012 and August 2012 (summer). We retrospectively analyzed relationships between their serum vitamin D levels and clinical parameters.ResultsThe serum 25-hydroxyvitamin D level in children with diabetes during winter was markedly lower than during summer (10.8±5.1 ng/mL vs. 17.6±5.6 ng/mL); vitamin D deficiency was more prevalent during winter (95% vs. 62%). However, there was no difference between children with diabetes and healthy children. In children with type I diabetes mellitus, among all the clinical parameters, age had the greatest negative correlation with serum vitamin D level.ConclusionIn children with diabetes, serum vitamin D levels showed marked seasonal variation. However, no clear relationship was identified between vitamin D deficiency and diabetes. This was because the control group had an equally high vitamin D deficiency rate. Additional studies including other clinical parameters after vitamin D supplementation in children with diabetes should be considered.